Handbook of Burns Volume 1 Acute Burn Care - Jeschke, Marc G.; Kamolz, Lars-Peter; Sjöberg, Folke; Wolf, Steven E. (Springer Vienna : Imprint: Springer, 2012)
This volume covers the entire spectrum of acute burn treatment. Individual chapters deal with basic aspects of different burn mechanisms as well as the acute care of burn patients. Pre-hospital management, critical care and basic concepts of burn surgery related to the acute phase, as well as the use of skin and skin substitutes in early stages of therapy are addressed in this volume. Chapters on supportive therapies such as optimizing nutrition and fluid homeostasis, infection control and treatment, respiratory support and pain management complete the comprehensive approach to the patient in this early stage of treatment, while chapters on epidemiology, prevention and disaster management enable the reader to evaluate the given information in a broader context.